The Pharmacology of Pain Associated With the Monoiodoacetate Model of Osteoarthritis - de Sousa Valente, João (Frontiers in Pharmacology, 2019)
The high incidence of OA in an increasingly elderly population anticipates that the number of patients suffering from pain associated with OA will rise dramatically in the near future. Pain management is crucial in the quality of life for many OA sufferers, reinforcing the need to develop preclinical models of OA that can be used to assess the efficacy of potential new therapeutics. Several animal models of OA have been developed but none of them reproduces entirely all symptoms of the disease. Choosing between different animal models depends largely on which aspect of OA one aims to study. There are several reasons why the MIA model of OA seems to be the most adequate to study the pain associated with OA. First, the pathological changes induced by MIA share many common traits with those observed human OA including loss of cartilage and alterations in the subchondral bone. Also the severity of the disease can easily be manipulated by altering the concentration of MIA used to induce the pathology. Further, the rapid induction of the disease state allows timely evaluation of pain modifying compounds. MIA injection in rodents leads to a chronic degeneration of the joint that is associated with chronic pain behaviour, namely altered hind limb weight bearing and induction of referred pain. Responsiveness of the MIA models to conventional pain-relieving therapies indicates that it may be useful for discerning therapeutic approaches. This model, therefore, may be more predictive for clinical efficacy than other chronic or acute pain models.